2022
DOI: 10.3389/fpls.2022.1010314
|View full text |Cite
|
Sign up to set email alerts
|

Leaf-transcriptome profiles of phoebe bournei provide insights into temporal drought stress responses

Abstract: Phoebe bournei (Hemsl.) Yang is used as a commercial wood in China and is enlisted as a near-threatened species. Prolonged droughts pose a serious threat to young seedlings (1-2 years old). A transcriptome sequencing approach, together with the measurement of growth parameters and biochemical analyses were used to understand P. bournei’s drought responses on 15d, 30d, and 45d of drought stress treatment. The stem and root dry weights decreased significantly with drought stress duration. Activities of antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…DEGs were enriched in soluble sugar-related and cell wall-related processes in P. massoniana under drought [ 58 ] . Drought stress inhibited the synthesis of Chla, Chlb and photosynthesis in Phoebe bournei [ 59 ]. In our study, the genes on the “Porphyrin and Chlorophyll metabolism” (ko00860) pathway were suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…DEGs were enriched in soluble sugar-related and cell wall-related processes in P. massoniana under drought [ 58 ] . Drought stress inhibited the synthesis of Chla, Chlb and photosynthesis in Phoebe bournei [ 59 ]. In our study, the genes on the “Porphyrin and Chlorophyll metabolism” (ko00860) pathway were suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of species distribution patterns showed that P. bournei is mainly distributed in the subtropics, with an annual average temperature of 15°C to 20°C and yearly precipitation of approximately 1505 mm ( Ge et al., 2014 ). Frequent extreme climate conditions and water scarcity have reduced the suitable areas for P. bournei , making afforestation difficult ( Li et al., 2022 ). Thus, it is essential to understand the regulatory mechanism of the stress response in P. bournei .…”
Section: Introductionmentioning
confidence: 99%
“…P. bournei grows in monsoon climates with abundant precipitation. However, its growth is affected by droughts and prolonged summers [ 49 ]. Studies have shown that global warming, caused by the rising global carbon dioxide concentrations due to the combustion of industrial fuels, significantly affects the incidence of forest fires and the efficiency of photosynthesis in forest trees [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that global warming, caused by the rising global carbon dioxide concentrations due to the combustion of industrial fuels, significantly affects the incidence of forest fires and the efficiency of photosynthesis in forest trees [ 50 , 51 ]. Additionally, global warming contributes to the dryness of the climate [ 49 ]. Drought has a significant impact on the dry weight of stems and roots, as well as chlorophyll synthesis and photosynthesis in P. bournei [ 52 ].…”
Section: Introductionmentioning
confidence: 99%